marketing public relations of Solo Grand Mall during the Covid 19 Pandemic - Rohman Rifai (Solidaritas, 2022)
ABSTRACT This study aims to describe and analyze the marketing public relations of Solo Grand Mall during the Covid 19 Pandemic. The background of the research is that the Marketing Public Relations of Solo Grand Mall optimizes delivery services from tenants to customers during the Covid-19 pandemic.The results of the study show that the Covid-19 pandemic has indeed changed many things, especially in doing business. Adjustment or adaptation to new habits is a must for every company if it wants to survive. Like during the Covid-19 pandemic, Solo Grand Mall. Through his Marketing Public Relations Strategy, he has managed to maintain his company's income so that it is in a financially secure position, although not as much as the previous year before the pandemic.Through the Pull, Push, Pass Strategy, conducted by the Marketing Public Relations of Solo Grand Mall, the company has enabled the company to further develop its capabilities, for example by creating a Petromindo.TV channel, holding online webinars, to continuing to meet face-to-face with clients while still paying attention to Health protocols. For further research, it may be possible to discuss the measurement of the effectiveness of marketing public relations promotions in Solo Grand Mall, so that it can be seen how successful it is. Keywords: Marketing Public Relations Solo Grand Mall